Culture and Psychopathology Revisited - Jilek, Wolfgang G. (Culture, 1983)
The author presents examples of pathogenic influence of culture. He identifies specific pathogenic factors associated with rapid socio-cultural change affecting North American Indians and African populations and sketches the resulting typical psychopathological conditions: anomic depression in Amerindians, transient psychotic reactions (bouffée délirante) in Africans. Witchcraft and sorcery beliefs often characterize the clinical picture of psychotic reactions in “marginal” Africans and in transplanted South Europeans of tradition-directed background. Examples are provided which illustrate the emergence, metamorphosis and epidemic spreading of so-called “culture-bound syndromes” under changing socio-economic, cultural and political conditions. Ritualized possession and trance states, as well as religious rituals in general, are to be separated from psychopathological phenomena in order to avoid eurocentric and positivistic fallacies in psychiatric diagnosis.